Frequency of Capillary leak syndrome in Dengue fever Patients - Safina Hameed Qureshi, Sania Hameed Qureshi, Syed Fahd Shah, Farid Ullah Shah, Syed Zubair Shah, Syed Hussain Shah (Journal of Rawalpindi Medical College, 2021)
Abstract Background: Dengue fever is the world’s fastest spreading mosquito borne viral infection. It is prevalent throughout both subtropical and tropical region if the world. The severe form of dengue fever with bleeding manifestations called as dengue hemorrhagic fever. Some of the Dengue fever patients developed capillary leak during critical period of illness. This study aims at determining the frequency of capillary leak syndrome in hospitalized dengue fever patients of tertiary care hospital. Patients and Methods: The study was conducted over a period of one month from 1st October to 30th October 2019 at department of Medicine Federal Government Polyclinic Post Graduate Medical Institute, Islamabad. This cross sectional study comprising 200 consecutive hospitalized (≥14 years of both gender) dengue fever patients. Results: Capillary leak syndrome found in 75 patients of Dengue fever. All of them were Primary Dengue Patients. Both ascites and effusion was present in 31 patients. Ascites only found in 25 patients, Pleural effusion bilateral in 7, Right sided pleural effusion in 11 and Left sided in 1 patient. None of the patient had pericardial effusion. Conclusion: It is concluded that capillary leak syndrome is common in primary dengue fever patients and its early diagnosis helps us in better management during critical phase of illness with better outcome. Key Words: Dengue Fever, Capillary Leak Syndrome, Dengue Shock